Analysis of The Application of Deradicalization And Constraints And Obstacles: A Case Study of Bandung Suicide Bombing - Hasibuan, Edi Saputra (SASI, 2023)
Introduction: The concept of deradicalization itself has been running for the first time since 2005 but there is no guide or patent concept for this program. The effect given through the deradicalization program must be recognized is not optimal, but this does not necessarily make deradicalization a failed innovation, keep in mind that the existence of the deradicalization program is an answer to the handling of terrorism that is considered hard and intimidative (hard approach), while the more subtle ways of dialogue and religious approach (soft approach) is considered also able to neutralize the values of terrorism in someone who is already radical.Purposes of the Research:  The real purpose of de-radicalization in general is to prevent repeated terror incidents by former prisoners, because the National Police itself has the task of being able to detect and prevent acts of violence that insurgents. Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approachResults of the Research: The deradicalization Program is not a program that can be assessed directly as a failed program, deradicalization must be remembered as a reflection of the bad and hard handling (hard approach) so that the form of humanism and respect for human rights can actually be reflected by the existence of deradicalization, with the existence of deradicalization also illustrates that the perpetrators of terror or ex-prisoners have hope to return to normal life, also indicates that the government pays attention to those who commit this crime.